Evaluation Of The Implementation Of Electronic Medical Resume For Chronic Diseases To Support Surveillance Of Non-Communicable Diseases In Welas Asih Regional Public Hospital, West Java Province - Amelia Nur Fauzia; Intan Pujilestari (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Electronic medical resumes are an important component of electronic medical records that support continuity of service and serve as a data source for non-communicable disease (NCD) surveillance activities. The completeness and quality of their completion directly impact the reliability of health information used for disease reporting and monitoring. This study aims to evaluate the implementation of electronic medical resumes for chronic disease patients to support non-communicable disease surveillance at Welas Asih Regional General Hospital, West Java Province. The study used a mixed methods approach with a sequential explanatory design. The study population was 2,399 electronic medical resumes of chronic disease patients from July–December 2025, with a sample of 96 resumes determined using the Slovin formula (10% error tolerance) and selected through proportional stratified random sampling across five chronic disease groups: Diabetes Mellitus, Hypertension, Stroke, Coronary Artery Disease (CAD), and Chronic Obstructive Pulmonary Disease (COPD). Quantitative data were collected through document observation using a checklist, while qualitative data were obtained through semi-structured interviews. The results showed an average overall completeness level of 90.03%, which is classified as very good. The level of completeness based on disease group was DM 89.88%, Hypertension 95.24%, Stroke 89.93%, CAD 95.24%, and COPD 95.24%. Based on component groups, patient identity reached 99.85%, treatment information 100%, clinical information 81.95%, and patient discharge condition 75%. Incompleteness was mainly found in the discharge diagnosis component, ICD-10 secondary diagnosis codes, and cause of death codes. Electronic medical resume data has been utilized for reporting, health statistics, diagnosis coding, and NCD surveillance. It is recommended to improve monitoring and compliance of healthcare workers in completing documents to optimize data quality